THE ‘BRITISH-IMPERIAL’ MODEL OF ADMINISTRATION: ASSEMBLING THE SOUTH AFRICAN CONSTABULARY, 1900 – 1902 - Spencer, Scott C (Scientia Militaria - South African Journal of Military Studies, 2013)
With the end of the South African War believed to be in sight, British policy makers in South Africa created the South African Constabulary (SAC) in late 1900 to provide law and order over the new Transvaal and Orange River colonies. By 1900, policy makers no longer simply exported ‘English’ or ‘Irish’ models to the colonies but sought guidance from existing institutions throughout the British Isles and Empire in a single ‘British-Imperial’ model of administration. Those policy makers and the new corps’ senior officers turned to the imperial policing network for ideas, methods, and particularly personnel to assemble the SAC, recruiting ten thousand officers and constables from across the British Isles and Empire. When it disbanded eight years later, SAC veterans used the imperial policing network to take up new positions in police forces throughout the British Isles and Empire. This ‘British-Imperial’ model implemented a ‘best practices’ form of administration in which the men (and, very occasionally, women) who carried these practices enjoyed superior importance.